2019
DOI: 10.1007/s00464-019-06766-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Simulation in Reverse and Side Alignment Impact on Forward Alignment Performance: A Randomized Controlled Trial

Abstract: Background-The influence of visual-spatial discordance during training on laparoscopic skills is poorly understood. It has been proposed that training in visual-spatial discordant situations can improve performance in the forward alignment, which was the basis of our hypothesis. Our study's aim was to conduct a randomized control trial to explore the impact of simulated training in visual-spatial discordant situations on forward alignment performance.Methods-The participants were 80 medical students who were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Additionally, we performed a test in the reverse alignment similar to our previous study to assess if the learning curve remains similar in different visual-spatial orientations [13]. As expected, RS performed significantly better likely owning to the ability of the robot to create a three-dimensional visualization.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, we performed a test in the reverse alignment similar to our previous study to assess if the learning curve remains similar in different visual-spatial orientations [13]. As expected, RS performed significantly better likely owning to the ability of the robot to create a three-dimensional visualization.…”
Section: Discussionmentioning
confidence: 80%
“…The first 40 students to respond and met the inclusion criteria were informed of the study objectives and time commitment, obtained informed consent, advised there would be no compensation, then were subsequently enrolled in the study. The sample size for the study was based on our previous study looking at the influence of visual-spatial discordance in LS [13]. Each participant completed a pre-performance questionnaire to collect demographic information (age, sex, college) and if they describe themselves as expert video-gamers (1 = strongly disagree through 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Except in the case of first-generation surgeons who started laparoscopic colorectal surgery, colorectal surgeons begin as assistants in laparoscopic colorectal surgery and overcoming visual-spatial discordance is an important task for these assistants. Several studies related to overcoming visual-spatial discordance have been reported [9,[11][12][13][14]. A study involving a video trainer reported that reverse alignment surgical skill can be improved through experience, but it is difficult to overcome through the residency training alone and training in the forward orientation does not help improve the reverse alignment surgical skill [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have reported that the mirror image can be overcome by rotating the screen displayed on the assistant’s monitor using an 180° image converter [ 11 ]. In a recent randomized controlled trial, an experiment was conducted to study whether laparoscopic technique training in reverse and side alignment conditions could improve the forward-alignment performance [ 14 ]. However, the results were inconclusive.…”
Section: Discussionmentioning
confidence: 99%